Effects of Freeze-thaw and Hydraulic Compound Action on Soil Erosion in Northern Rocky Mountainous Area - YANG Haoyu; MA Lan; CHEN Shiyuan (Shuitu Baochi Xuebao)
[Objective] This study aims to elucidate the impact of freeze-thaw cycles and hydraulic action on soil erosion in the northern rocky mountain regions under varying conditions. [Methods] Utilizing soil samples from the Jiufeng area in Beijing, we conducted simulation tests using indoor runoff scouring and freeze-thaw equipment. We examined the effects of five key factors—freeze-thaw cycle frequency, slope gradient, flow rate, initial soil moisture content, and freeze-thaw temperature differential—on soil sediment yield and anti-scourability. [Results] (1) The sensitivity of the soil’s anti-scourability coefficient to these factors ranks as follows: slope>flow rate>freeze-thaw temperature difference>freeze-thaw cycles>initial moisture content. Notably, slope and flow rate significantly influence the coefficient (p<0.05). For soil sediment yield, the sensitivity ranking is: flow rate>slope>freeze-thaw temperature difference>soil moisture content>freeze-thaw cycles, with flow rate exhibiting a very significant impact (p<0.01), and both slope and freeze-thaw temperature difference showing significant effects (p<0.05). (2) The number of freeze-thaw cycles, slope, and flow rate negatively correlate with the soil's anti-scour coefficient, whereas the temperature difference during freeze-thaw cycles positively correlates with it. The anti-scour coefficient initially decreases and then increases with rising initial soil moisture content. (3) Soil sediment yield increases with higher discharge rates, steeper slopes, and more frequent freeze-thaw cycles, but decreases with an increase in the overall temperature of the freeze-thaw differential. As soil moisture content rises, sediment yield initially increases and then decreases. When the number of freeze-thaw cycles reaches 7 or 10, sediment yield peaks (96.7~99.7 g/min) during the middle phase of runoff scouring (3~6 min) and then stabilizes. [Conclusion] Soil in the northern rocky mountain areas is significantly impacted by various factors under the combined effects of freeze-thaw and hydraulic pressures. The findings of this study provide valuable theoretical support for the prevention and management of combined erosion and for the strategic allocation of soil and water conservation measures in these regions.